Efficient Differentiation of Human Pluripotent Stem Cells to Endothelial Progenitors via Small-Molecule Activation of WNT Signaling - Lian, Xiaojun (Stem Cell Reports, 2014)
Human pluripotent stem cell (hPSC)-derived endothelial cells and their progenitors may provide the means for vascularization of tissue-engineered constructs and can serve as models to study vascular development and disease. Here, we report a method to efficiently produce endothelial cells from hPSCs via GSK3 inhibition and culture in defined media to direct hPSC differentiation to CD34(+)CD31(+) endothelial progenitors. Exogenous vascular endothelial growth factor (VEGF) treatment was dispensable, and endothelial progenitor differentiation was β-catenin dependent. Furthermore, by clonal analysis, we showed that CD34(+)CD31(+)CD117(+)TIE-2(+) endothelial progenitors were multipotent, capable of differentiating into calponin-expressing smooth muscle cells and CD31(+)CD144(+)vWF(+)I-CAM1(+) endothelial cells. These endothelial cells were capable of 20 population doublings, formed tube-like structures, imported acetylated low-density lipoprotein, and maintained a dynamic barrier function. This study provides a rapid and efficient method for production of hPSC-derived endothelial progenitors and endothelial cells and identifies WNT/β-catenin signaling as a primary regulator for generating vascular cells from hPSCs.